Nitrogen efficiency in marandu palisadegrass pastures under increasing nitrogen levels - de Quadros, Fernando Luiz Ferreira; Ongaratto, Fernando; Malheiros, Euclides Braga [UNESP]; Lima, Laís de Oliveira; Dallantonia, Erick Escobar; Romanzini, Eliéder Prates; Velludo, Igor de Martin; Cardoso, Abmael da Silva; Do Val, Guilherme Alves [UNESP]; Rigobello, Izabela Larosa [UNESP]; Fernandes, Márcia Helena Machado da Rocha [UNESP]; Reis, Ricardo Andrade [UNESP] (FapUNIFESP (SciELO), 2024)
The use of nitrogen (N) in pastoral ecosystems leads to increased productivity, as it allows the plant to elongate its leaves and, therefore, grazing herbivores harvest the green leaves. However, there are very volatile N sources, which can be replaced by ammonium nitrate, which is less volatile and less dependent on the application in rainy days. The treatments are compound of Marandu palisade grass pastures managed under continuous stocking at a canopy height of 25 cm, with different levels of N fertilizer: 0, 75, and 150 kg ha-1 year-1, as ammonium nitrate (32% of N), with four replicates (pastures) in a completely randomized design. Nitrogen uptake (54.9, 96.5, 113.8 kg N ha-1) and N nutrition index (0.67, 0.98, 1.15) were different between N level, respectively, 0, 75 and 150 kg ha-1 year-1. The N recovery (58.3, 40.9 %) differed between 75 and 150 kg ha-1 year-1, respectively. The dose of 75 kg N kg ha-1 year-1 results in better N utilization, while the dose of 150 kg N ha-1 year-1 enables greater stocking rate; therefore, requiring less grazing area.
Eficiência do nitrogênio em pastagens de capim-marandu adubadas com doses crescentes de nitrogênio
Keywords: beef cattle; canopy; nitrogen nutrition index; nitrogen recovery; sustainability; Urochloa